(untitled) (Academia Journal of Medicine, 2023)
3D printing technology has emerged as a transformative force in the field of dentistry, offering unprecedented advancements in precision, customization, and patient care. This evidence-based article explores the impact of 3D printing in dentistry, supported by recent studies and research. The utilization of 3D printing has led to superior precision in the fabrication of dental prosthetics, customized patient-specific care, and improved surgical planning through the creation of guides. Furthermore, advancements in material science have ensured the biocompatibility and durability of 3D printed dental materials. While promising, challenges such as regulatory standards, material safety, and cost effectiveness warrant consideration. The evidence presented underscores the potential of 3D printing to revolutionize the field of dentistry, offering a glimpse into a future defined by personalized, efficient, and effective dental treatments.